Respuesta :
Answer:
[tex]x = - 3[/tex]
[tex]y = 1[/tex]
Step-by-step explanation:
Write the system
[tex]3x - y = - 10[/tex]
[tex]x + y = - 2[/tex]
Solve by Elimination.
multiply the second equation by -3.
[tex]3x - y = - 10[/tex]
[tex] -3x - 3y = 6[/tex]
Add the Equations.
[tex] - 4y = - 4[/tex]
[tex]y = 1[/tex]
Plug this back in one of the equations.
[tex]x + 1 = - 2[/tex]
[tex]x = - 3[/tex]
Answer:
x = -3
y = 1
Step-by-step explanation:
3x - y = -10
x + y = - 2
x + y = - 2
x = -y - 2
replacing in other equation
3(-y - 2) - y = -10
-3y - 6 - y = - 10
rearranging the equation
-3y - y = = -10 + 6
-4y = -4
y = 1
putting this value in first eqn we get
x - y = -2
x - (1) = -2
x = -2-1
x = -3